SISTEM FULL DAY SCHOOL/FDS SMP IT NURUL ISLAM DESA KLERO KECAMATAN TENGARAN KABUPATEN SEMARANG PROVINSI JAWA TENGAH - TITIN JAMALIS SURURIAH; AGUS SUJARWO; MUJIATUN (UNISAN JURNAL, 2022)
The main goal of education is to establish a solid foundation for a person’s character through the internalization of values, the development of emotional and spiritual intelligence, and the resulting influencing of how they live their lives. The "full day" program is now being used in a number of elementary/mi, junior high/mts, and high school/ma schools around the nation. Some modern folks who are busy working outside the home have responded favorably to this school. In the hopes of addressing the kid’s developmental requirements, imparting religion and values to the child, and maximizing their child’s development, parents enroll their children in full-day schools. As a result, the research in this thesis focuses on a number of issues, including: (1) How is the full-day school system’s input? (2) What is the full-day school system’s management process? and (3) What are the outcomes of the full-day school system’s implementation? Because of this, the author’s research approach for producing this thesis was a qualitative discriminatory research method, with an emphasis on the power of direct field observation followed by data analysis. The findings of this study, which were based on the observations of human resources researchers, show that SMPIT Nurul Islam’s students, teachers, and educational personnel are doing well. The SMPIT Nurul Islam education personnel, teachers, and students receive good human resource input view the organizational structure, the curriculum, the employees, the facilities, and the leader, specifically the principle. The SMPIT Nurul Islam learning process lasts the entire day, from 07.30 to 15.30. Many people are interested in SMPIT Nurul Islam’s educational programs. Nurul Islam is taught the TPA curriculum at SMPIT in addition to teachings from the ministry of religion and